The rise of autobiography in the Eighteenth century : ten experiments in literary genre - Augustine, Bunyan, Rousseau, Locke, Hume, Franklin, Gibbon, Fielding, Sterne, Boswell - Bell, Robert H. (Robert Huntley), 1946- (Edwin Mellen Press, 2012)
Bell utilizes an inter-disciplinary approach to studying autobiography in the 18th Century. Making use of religion and philosophy, history and literature, contemporary theory and humanism, his original analysis offers a unique array of disciplinary interpretations of the genre. This book not only deals with autobiography in a thorough manner, it also incorporates historical and philosophical interpretations to the presentation of self in this type of literature. He also demonstrates some of the problems with first person singular writing, which distinguishes this style from other forms of non-
Keywords: Autobiography -- History -- 19th century.; Biography as a literary form.; Autobiography -- Authorship.; Biography.; Biographies as Topic.; Autobiographie -- Histoire -- 19e siècle.; Biographie (Genre littéraire); Biographies.; biographies (literary genre); biography (general genre); BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Autobiography; Autobiography -- Authorship; Biography as a literary form; History & Archaeology.; Biography - General.; 1800-1899; History